Communication Behaviour of Dairy Farmers: A Source for Milk Qulity Improvement - Singh, Vikram; Gupta, Jancy; Nain, M. S. (Indian Journal of Extension Education, 2014)
The present study was conducted in dairy cooperative system of Rajasthan state in organized sector i.e. Rajasthan  Cooperative Dairy Federation (RCDF). A multistage proportionate random sampling procedure was applied to draw the  sample for the study. Out of 21 unions four district milk unions were selected for the present study viz. Alwar, Bhilwara,  Bikaner and Hanumangarh. A total of 120 farmers were selected on the basis of proportionate random sampling. The  results of this study revealed that most of the dairy farmers used friends, progressive milk producers, veterinary officers  and neighbours as information sources; group discussion, group meetings, newspaper and Dairy Cooperative Society  (DCS) were important channels for information seeking about proper 'cattle shed' and 'milking procedure'. However, Milk  route supervisor, progressive milk producer, friends and neighbours were found as major information sources; whereas,  DCS, educational tour and group discussion were important channels for information used by the dairy farmers for  information seeking about 'cleaning of utensil' and 'post milking practices'.